Analisis Kesalahan Dalam Menyelesaikan Soal Identitas Trigonometri Berdasarkan Kriteria Watson (Siswa-Siswi kelas X SMAN Tamalabang tahun ajaran 2022/2023) - Puling Tang, Melki Imamastri (Sepren, 2024)
In this study, researchers will find out the obstacles faced by students when working on trigonometric identity problems based on Watson criteria. The method in research is qualitative description through several conditions, namely data reduction, data presentation, and conclusions. Based on the results of the study, it was found that among the 8 types of Watson error criteria, students made the most errors on several criteria, namely incorrect data, improper procedures, missing data and missing conclusions. This error can occur because students are lacking in mastering the concept of trigonometric identity material, so students often make mistakes from entering data that has been known to the problem, students are unable to apply formulas in solving problems, also students cannot solve the problem until the end. The factors causing the error of class XI students of Tamalabang State Science in solving trigonometric identity problems are students who do not master the basic concepts of trigonometric identity and students do not want to learn to understand the basic concepts of trigonometric identity because students find it difficult to understand, causing students to often make mistakes.